Spheroidal graphite coalescence during thermal cycling in the ferritic domain of a high-silicon cast iron studied by optical microscopy and X-ray computed tomography. (December 2020) - Pegoraro, Mariana Alves; Tenailleau, Christophe; Ebel, André; Malard, Benoit; Lacaze, Jacques
Graphical abstract: Highlights: Spectacular coalescence of spheroidal graphite nodules in high silicon cast iron . 3000 thermal cycles at 800 °C led to particles growth and dendritic protuberances. Optical microscopy and X-ray Computed Tomography useful to study the microstructures. An isothermal treatment keeps the graphite particles round in shape. Half of the particles lose their circularity and sphericity after thermal cycling. Abstract: High-silicon cast irons remain ferritic at higher temperature than usual cast irons and present both better oxidation resistance and higher mechanical strength. Such a high-silicon spheroidal graphite cast iron was heat treated up to 50 h in total at 800 °C in two different manners: under isothermal and cyclic conditions. Under the isothermal condition, the distribution of graphite inclusions did not vary significantly. On the contrary, temperature cycling led to spectacular coalescence whose evolution was observed after 1000, 2000 and 3000 cycles. Quite unexpectedly, the largest graphite particles - that were growing because of coalescence - showed an irregular outer surface after 1000 cycles, which evolved in impressive dendritic instabilities and then large protuberances after 2000 and 3000 cycles. Optical microscopy and X-ray computed tomography (XCT) were used to quantitatively study these microstructural changes.